Interest Rate Transmission Mechanism of Monetary Policy in the Selected EMU Candidate Countries - Mirdala, Rajmund (Panoeconomicus, 2009)
The stable macroeconomic environment, as one of the primary objectives of the Visegrad countries in the 1990s, was partially supported by the exchange rate policy. Fixed exchange rate systems within gradually widen bands (Czech Republic, Slovak Republic) and crawling peg system (Hungary, Poland) were replaced by the managed floating in the Czech Republic (May 1997), Poland (April 2000), Slovak Republic (October 1998) and fixed exchange rate to euro in Hungary (January 2000) with broad band (October 2001). Higher macroeconomic and banking sector stability allowed countries from the Visegrad group to implement the monetary policy strategy based on the interest rate transmission mechanism. Continuous harmonization of the monetary policy framework (with the monetary policy of the ECB) and the increasing sensitivity of the economy agents to the interest rates changes allowed the central banks from the Visegrad countries to implement monetary policy strategy based on the key interest rates determination. In the paper we analyze the impact of the central banks’ monetary policy in the Visegrad countries on the selected macroeconomic variables in the period 1999-2008 implementing SVAR (structural vector autoregression) approach. We expect that higher sensitivity of domestic variables to interest rates shocks can be interpreted as a convergence of monetary policies in candidate countries towards the ECB’s monetary policy. Key words: Monetary policy, Short-term interest rates, Structural vector autoregression, Variance decomposition, Impulse-response function. JEL: C32, E52.